Studi kinerja katalisator lewatit monoplus s-100 pada reaksi esterifikasi antara etanol dan asam asetat - Nuryoto Nuryoto (Jurnal Rekayasa Proses, 2008)
Sulfuric acid is common catalyst in producing ethyl acetate. Despite of high conversion, using sulfuric acid as catalyst is appearing a lot of problems. The use of solid catalyst is expected to solve the problem. Utilizing of lewatit monoplus s-100 in the esterification of ethanol and acetic acid was investigated in this work. The experiments were carried out in a reactor on the hot plate equipped with magnetic stirrer. The reactant ratio was 1.2 gmol acetic acid / gmol ethanol and lewatit monoplus s-100 as catalyst. Samples were taken at initial and after 60 minutes, then the samples were analyzed by using gas chromatograph. The same experiments were conducted at different temperatures and catalyst concentrations. Based on the experimental result, lewatit monoplus s-100 performed well as solid catalyst in the esterification. It was shown that the higher the temperature, the higher the reaction rate, meanwhile increasing the catalyst concentration, the conversion was lower. The highest conversion was 87.3%, when the temperature was 358 K, and a catalyst concentration was 0.8 g. resin /g. ethanol.